Penentuan Harga Jual Kendaraan Bekas Jenis Vespa Classic di Wilayah Buleleng - Ida Bagus Diddo Kusuma; Nyoman Ari Surya Darmawan (Jurnal Ilmiah Akuntansi dan Humanika, 2022)
This study aims to find out how to determine the selling price of a used vespa classic according to a vespa classic seller and also interview one of the vespa classic buyers in buying an old but rare and expensive vehicle on the market that trades two-wheeled vehicles. The approach used is a descriptive qualitative approach. Data collection techniques were carried out through observation, interviews and documentation studies. Data analysis techniques used are data reduction, data presentation, and drawing conclusions. The research subject is the owner of the Vespa D n A workshop as well as the seller of the classic vespa and the buyer of the classic vespa vehicle. The results showed that 1) In determining the price of a used vehicle, the classic Vespa type was in accordance with the theoretical criteria of cost of goods sold and the determination of the selling price 2) The results based on interviews that have been conducted with one of the classic Vespa consumers stated that the current attractiveness of the classic Vespa is high because this vehicle has not been produced by the factory since 2007 which gives an antique and rare impression, so that consumers dare to buy the vehicle at a relatively high price